Archaeological investigations at the Ljubljana site on Ljubačka kosa (In situ, 2025)
The paper presents the results of archaeological research carried out as part of the fieldwork practice for archaeology students during the year 2024 at the Ljubljana site on Ljubačka kosa.
Keywords: Ljubljana; Ljubačka kosa; Late Antiquity; Middle Ages; Modern Period; St. Marcella; St. Mary